Hotwork Permit Issuance Mechanism at KSOP On Ship Mv. Zhong Quan 7 By PT. Pelayaran Dwi Putra Laksana Batam - Febrian Nababan; Syarifur Ridho; Lilis Lilis (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This paper examines the Hotwork Permit Issuance Mechanism on the Zhong Quan 7 Ship. This study aims to determine the Hotwork Permit Issuance Mechanism on the Zhong Quan 7 Ship by PT. Pelayaran Dwi Putra Laksana Batam, and to find out if there are any obstacles in the Hotwork Permit Issuance Mechanism on the Zhong Quan 7 Ship by PT. Pelayaran Dwi Putra Laksana Batam. The research method uses field research methods (Field Research) and library research (Library Research). The results of this study are the Hotwork Permit Issuance Mechanism at KSOP on the MV Ship. Zhong Quan 7. Starting with the agent submitting an application for a welding permit at KSOP through the Inaportnet system and then the agent also submits a manual application to the Harbor Master's Office Post in the work area where the ship will dock for unloading activities. Hotwork Permit is needed for cargo safety welding activities on the MV ship. Zhong Quan 7. The data collection techniques used are library research and field research.